2011
DOI: 10.1080/00220388.2010.506912
|View full text |Cite
|
Sign up to set email alerts
|

Within-Firm Human Capital Externalities in Tunisia

Abstract: This case study exploits matched firm-employee Tunisian data in order to underline the role played by within-firm human capital in worker remuneration. The estimated returns to human capital in wage equations remain unchanged when the dummies representing firm heterogeneity are replaced in the list of regressors with three firm variables: a textile industry dummy, within-firm mean education, and firm age. We find that part of what is usually considered as return to education may be due to within-firm externali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…One study that did touch on training in a MENA country (Tunisia) is Muller and Nordman (2011). These authors identified cases where such training did take place and showed that this was where wage rates were generally low during training but higher afterwards, thereby supporting the explanation of Acemoglu and Pischke (1998).…”
Section: Some Empirical Studies On Such Training In Developing Countriesmentioning
confidence: 49%
“…One study that did touch on training in a MENA country (Tunisia) is Muller and Nordman (2011). These authors identified cases where such training did take place and showed that this was where wage rates were generally low during training but higher afterwards, thereby supporting the explanation of Acemoglu and Pischke (1998).…”
Section: Some Empirical Studies On Such Training In Developing Countriesmentioning
confidence: 49%
“…The full list of papers and their details can be found in Appendix A. See also Muller and Nordman (2011) which includes two estimates using IV.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…With such a special specification and a basic set of correlates, we found a preliminary evidence of correlation of OJT with current wages. Similarly, Muller and Nordman (2011) include OJT variables in current wage equations, while focusing on withinfirm human capital externalities. However, in these previous studies, the dynamic dimension of the data on wages was not exploited, in particular the possibility of combining the employees' starting and current wages in the analysis.…”
Section: Wage Determinationmentioning
confidence: 99%